Evaluasi Kualitas Website IKIP Budi Utomo Malang menggunakan Metode Webqual 4.0 dan Importance Performance Analysis (IPA) - Amrta Ageng Subarkah; Retno Indah Rokhmawati; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Website IKIP Budi Utomo Malang is a website that provides information services to give various conveniences for IKIP Budi Utomo Malang's members, between campus institutions and external users. Based on the observations of researchers on the website, that the features and function on the website have not functioned optimally. So, the efforts of this research are to improve the quality of website services that need to be improved based on end-user perceptions with the aim of obtaining information on the results of the evaluation of the Budi Utomo Malang IKIP website using the Webqual 4.0 method and Importance Performance Analysis (IPA) and providing recommendations for improvement using the HHS Guidelines. The data obtained from the results of the end user's perception, by providing an evaluation of the level of performance and importance in 19 attributes of Webqual 4.0, obtained up to 106 respondents and were calculated by the IPA method. The evaluation results of the Budi Utomo Malang IKIP website have 4 quadrants : Quadrant 1 gets 6 attributes, Quadrant 2 gets 4 attributes, Quadrant 3 gets 5 attributes, and Quadrant 4 gets 4 attributes, which is on Quadrant 1 is the main priority that used as a recommendation to improvement using the HHS Guidelines, because the attributes of this quadrant have a relatively high level of importance, but not suitable with user expectations and the level of performance must be increased.